2017
DOI: 10.1111/zph.12380
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofSalmonellaamong waterfowl along the Texas Gulf coast

Abstract: Migratory waterfowl may play a role in the ecology and transmission of zoonotic pathogens, given their ability to travel long distances and their use of varied habitats. Our objectives were to estimate the prevalence of Salmonella among waterfowl along the Texas Gulf coast and to characterize the isolates. Faecal samples were collected from hunter-harvested waterfowl at four wildlife management areas from September through November, 2016. Standard bacteriologic culture methods were used to isolate Salmonella f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The most frequently isolated serotype was S. Kentucky. Other studies in the USA [33,34] have reported a lower prevalence (8/342, 2%, and 2/375, 0.5%) of Salmonella in free-living waterfowl. Furthermore, in Chile, a prevalence of 6% was reported by Fresno et al [35].…”
Section: Prevalence Of Salmonella In Waterfowlsmentioning
confidence: 77%
See 1 more Smart Citation
“…The most frequently isolated serotype was S. Kentucky. Other studies in the USA [33,34] have reported a lower prevalence (8/342, 2%, and 2/375, 0.5%) of Salmonella in free-living waterfowl. Furthermore, in Chile, a prevalence of 6% was reported by Fresno et al [35].…”
Section: Prevalence Of Salmonella In Waterfowlsmentioning
confidence: 77%
“…Al Faruq et al [11] recorded that the resistance rate of KF was 30-67% from Asian pied starling and house crows that were caught in Bangladesh. Grigar et al [34] isolated S. Thompson and Salmonella Braenderup, and both isolates were susceptible to all antimicrobial agents tested. Fasaei and Tamai [1] recorded that 42.8% of Salmonella isolated from wild animals in Iran were resistant to AML.…”
Section: Antimicrobial Susceptibility Of Salmonella Isolatesmentioning
confidence: 98%
“…Concomitant disease is discussed to increase the susceptibility to salmonellosis 6 . Infections with Salmonella have also been reported for various aquatic birds, 6, 15–18 including an outbreak in a heron colony involving six different heron species 19 . For both Salmonella positive passerine birds, a greenfinch and a house sparrow, no clinical history or age was noted.…”
Section: Discussionmentioning
confidence: 99%
“…However, many reports on Salmonella in poultry mainly focused on chickens and turkeys ( Barrow et al., 2012 ). Recent studies have shown that waterfowl such as geese and ducks are also important sources of Salmonella ( Grigar et al., 2017 ). Salmonella infection in geese and ducks is a recessive infection, but sometimes it can also have serious clinical symptoms with high mortality, and become the hidden danger of human health ( Martelli et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%